2018
DOI: 10.1007/s00382-018-4393-y
|View full text |Cite
|
Sign up to set email alerts
|

Zonally asymmetric trends of winter total column ozone in the northern middle latitudes

Abstract: Using various satellite-based observations, a linear ozone transport model (LOTM), a chemistry-climate model (WACCM3) and an offline chemical transport model (SLIMCAT), zonally asymmetric trends of the total column ozone (TCO) in the northern middle latitudes during winter for the period 1979-2015 are analyzed and factors responsible for the trends are diagnosed. The results reveal that there are significant negative TCO trends over the North Pacific and positive TCO trends over the northwestern North America.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 83 publications
5
27
0
Order By: Relevance
“…Compared to the TCO trends in January and March, the trends in TCO in February show a more asymmetric structure in the high latitudes with a strong TCO decline over Siberia. This feature is consistent with the conclusion of Zhang et al (2016Zhang et al ( , 2018Zhang et al ( , 2019b) that the shift of the Arctic stratospheric polar vortex toward Eurasia is more significant in February. Considering that the most significant ZAO trend occurs in February, we will now focus on the impacts of ZAO changes on the polar vortex in that month.…”
Section: Impacts Of Stratospheric Ozone Changes On the Polar Vortexsupporting
confidence: 92%
See 3 more Smart Citations
“…Compared to the TCO trends in January and March, the trends in TCO in February show a more asymmetric structure in the high latitudes with a strong TCO decline over Siberia. This feature is consistent with the conclusion of Zhang et al (2016Zhang et al ( , 2018Zhang et al ( , 2019b) that the shift of the Arctic stratospheric polar vortex toward Eurasia is more significant in February. Considering that the most significant ZAO trend occurs in February, we will now focus on the impacts of ZAO changes on the polar vortex in that month.…”
Section: Impacts Of Stratospheric Ozone Changes On the Polar Vortexsupporting
confidence: 92%
“…Using numerical model simulations, most previous studies only found significant regional surface responses over the northern middle and high latitudes when comparing cases of extremely high and low Arctic stratospheric ozone (Cheung et al 2014;Karpechko et al 2014;Smith and Polvani 2014;Calvo et al 2015;Xie et al 2016Xie et al , 2017Harari et al 2019). One possible reason is that the dynamical variability of the Arctic stratospheric polar vortex is much larger than its Antarctic counterpart (Hu and Guan 2018;Hu et al 2019a;Mai et al 2020) and as a result Arctic stratospheric ozone depletion is less persistent than Antarctic ozone depletion (Manney et al 2011). Therefore, one would expect a weaker impact of ozone depletion on surface conditions in the Northern Hemisphere compared to the Southern Hemipshere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, following the implementation of the Montreal Protocol in 1987, signs of an ozone recovery have been reported in recent years (WMO,70 2014; Chipperfield et al, 2015Chipperfield et al, , 2017Solomon et al, 2016;Kuttippurath and Nair, 2017;Pazmiño et al, 2018;Strahan and Douglass, 2018;Weber et al, 2018). Outside of the polar regions, column ozone amounts are largely determined by the stratospheric dynamics and hence quantifying long-term trends is quite challenging Rex et al, 2004;Manney et al, 2011;Zhang et al, 2016Zhang et al, , 2018Zhang et al, , 2019. Observations and model simulations 75…”
Section: Introductionmentioning
confidence: 99%